Importance of residents' satisfaction for supporting future tourism development in rural areas of Hong Kong. Issue 2 (3rd July 2019) - Chow, Alice S.Y.; Liu, Shuwen; Cheung, Lewis T.O.
ABSTRACT: Developing tourism in rural areas is an important approach to offering revitalization opportunities for many rural areas. A successful tourism development plan can offer economic benefits to rural communities through enhancing business and job opportunities. Our study in a popular rural tourism destination in Hong Kong intended to test the importance of residents' satisfaction, which may lead to their support for future tourism development in their community. The results of structural equation modeling suggested that residents' perceived impacts were not significantly associated with their support for future tourism development. In contrast, residents' satisfaction was significantly associated with their support for such development, implying that local residents' satisfaction with existing tourism development can be an important predictor for their further support of such development. As an important predicator influencing community support, residents' satisfaction with tourism deserves more attention not only from academic researchers but also from government and the tourism industry.